2018
DOI: 10.4046/trd.2017.0088
|View full text |Cite
|
Sign up to set email alerts
|

Different Pattern of Chronic Obstructive Pulmonary Disease Assessment Test Score between Chronic Bronchitis and Non-chronic Bronchitis Patients

Abstract: BackgroundChronic bronchitis (CB) is an important phenotype in chronic obstructive pulmonary disease (COPD). The purpose of this study is to evaluate different pattern of COPD assessment test (CAT) score between CB and non-CB patients.MethodsPatients were recruited from 45 centers in Korea, as part of the Korean COPD Subgroup Study cohort. CB was defined when sputum continued for at least 3 months.ResultsTotal 958 patients with COPD were eligible for analysis. Among enrolled patients, 328 (34.2%) were compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…These clinical characteristics of CB corresponded to those of patients with CB in previous studies. [12][13][14][15]29,32 Furthermore, the RV/ TLC was significantly higher in the CB group CB than the non-CB group classified according to the CAT definition (P<0.05). Although the same tendency was observed with the other definitions, it was not statistically significant in either case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These clinical characteristics of CB corresponded to those of patients with CB in previous studies. [12][13][14][15]29,32 Furthermore, the RV/ TLC was significantly higher in the CB group CB than the non-CB group classified according to the CAT definition (P<0.05). Although the same tendency was observed with the other definitions, it was not statistically significant in either case.…”
Section: Discussionmentioning
confidence: 99%
“…3 Goblet cell hyperplasia in the bronchial epithelium is an important pathophysiological mechanism underlying this phenotype, which results in hypersecretion of mucus leading to airway obstruction and a predisposition to bacterial colonization. 3,[9][10][11] Recent reports indicated that CB phenotype is associated with poor health-related quality of life, 3,[12][13][14][15] reduced lung function, 12,14 more frequent exacerbations, 3,7,12,14,16,17 and higher mortality rate. 14,16 These CB patients have been reported to constitute 14-74% of all COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…33 CAT scores for patients with chronicbronchitis-type and chronic-bronchitis-free-type COPD were investigated, and they were higher for responses to all of the eight questions in chronic-bronchitis-type, although there were no differences in lung function. 34 Since the proportion of current smokers was high (41.8%) among subjects with chronic cough and phlegm, smoking cessation is necessary in addition to medical treatment. The proportion of subjects who attempted to quit smoking in the past year was 23.0% in Japan, 35 which was lower than that in the United Kingdom 36 and the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic bronchitis patients with COPD are characterized by airway wall thickening as detected via thoracic CT. 6,14 Such patients are often more symptomatic and show more frequent exacerbations compared to patients without chronic bronchitis. [24][25][26][27] Furthermore, MWA% is also correlated with small airway disease, 10 and it may also have had a detrimental effect on COPD patients with mixed phenotype. We found that frequent exacerbations in the mixed phenotype may have led to increased mortality, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%